Characterisation of a Nickel-iron Battolyser, an Integrated Battery and Electrolyser - Barton, John P.; Gammon, Rupert J. L.; Rahil, Abdulla (Frontiers in Energy Research, 2020)
Electricity systems require energy storage on all time scales to accommodate the variations in output of solar and wind power when those sources of electricity constitute most, or all, of the generation on the system. This paper builds on recent research into nickel-iron battery-electrolysers or “battolysers” as both short-term and long-term energy storage. For short-term cycling as a battery, the internal resistances and time constants have been measured, including the component values of resistors and capacitors in equivalent circuits. The dependence of these values on state-of-charge and temperature have also been measured. The results confirm that a nickel-iron cell can hold 25% more than its nominal charge. However, this increased capacity disappears at temperatures of 60°C and may be dissipated quickly by self-discharge. When operating as an electrolyser for long-term energy storage, the experiments have established the importance of a separation gap between each electrode and the membrane for gas evolution and established the optimum size of this gap as approximately 1.25 mm. The nickel-iron cell has acceptable performance as an electrolyser for Power-to-X energy conversion but its large internal resistance limits voltage efficiency to 75% at 5-h charge and discharge rate, with or without a bubble separation membrane.